2022
DOI: 10.3390/ijpb13020014
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Relationships in the Wood of Four Siberian Conifers: Whether Elements Are an Occasional Mixture

Abstract: In the abundant literature on plant chemistry, little attention is paid to correlations among chemical elements in tissues. The goal of the research is to establish consistent correlations among elements in the xylem of four widespread Siberian conifers. X-ray fluorescent analysis has been applied to find out the elements contained in the xylem. The method allowed finding the mean count rates of Al, P, S, K, Ca, Ti, Mn, Fe, Cu, Zn, and Sr in trunks of trees. Moreover, the xylem samples were chemically treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Due to its polar form with partial positive charges on the hydrogens, a partial negative charge on the oxygen and a bent overall structure, water for example, mainly dissolves ions and polar molecules like salts. Therefore pectinates and oxalates of various metals present in the intercellular space of wood (Gavrikov et al, 2022) as well as other crystals might be more efficiently extracted by water compared to metals present in different atomic form in the cell walls.…”
Section: Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its polar form with partial positive charges on the hydrogens, a partial negative charge on the oxygen and a bent overall structure, water for example, mainly dissolves ions and polar molecules like salts. Therefore pectinates and oxalates of various metals present in the intercellular space of wood (Gavrikov et al, 2022) as well as other crystals might be more efficiently extracted by water compared to metals present in different atomic form in the cell walls.…”
Section: Alcoholmentioning
confidence: 99%
“…(1993) to reduce the biasing influence of translocation processes of elements in dendrochemical time series. If applied, it could be shown that this chemical pretreatment of wood samples increased correlations between element profiles in different conifer species (Gavrikov et al, 2022). In another study Belt et al (2017) could visualize the influence of an extraction on the concentration of extractives present in pine heartwood, so called pinosylvins.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, X-ray fluorescence spectroscopy maintains its efficacy as an effective method for elemental investigation of wood and subfossil wood (Pereira Junior. et al 2016, Zielenkiewicz et al 2012, Mustoe 2023, Gavrikov et al 2022. Subfossil wood refers to wood that has undergone partial fossilization but has not been yet fully mineralized to become a true fossil.…”
Section: Introductionmentioning
confidence: 99%